THE USE OF LANGUAGE LEARNING STRATEGIES TOWARDS STUDENTS’ ENGLISH ACADEMIC ACHIEVEMENT AT SMA NEGERI 1 BAUBAU - Esa Penilta Amiruddin; Sanaria Maneba (English Education Department, 2020)
The aim of this study was to what extent language learning strategies used by students give an impact on their English academic achievement. The instrument of the research was achievement test and interview. The intention of the researchers to take the achievement test was to find out English academic achievement of learners (English grade) in second semester academic year 2019/2020. The second instrument for gathering data concerning students’ strategies was semi-structured interview. In conclusion, 45 % of the variance in the English academic achievement of IPA 1 students can be explained by the language learning strategies used, while 57 % the variance of the English academic achievement of IPA 2 students can described by the LLS employed.